2016
DOI: 10.1097/mib.0000000000000767
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Options and Outcomes of Pediatric IBDU Compared with Other IBD Subtypes

Abstract: Children with IBDU have a lower medication burden and lower surgery rates than other IBD subtypes. The disease course at follow-up is generally mild, supporting an initial trial with 5-ASA before using more aggressive therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Given the rarity of IBDU and the hitherto lack of standardized diagnosis, there are very few studies which have been able to collect treatment information on significant numbers of patients. The aforementioned retrospective study from the Porto group of ESPGHAN utilized the data of 537 children with colonic IBD, including 260 IBDU, to explore common treatment schemes and to compare the treatment outcomes (298). This study demonstrated that treatment for IBDU and UC were broadly similar with the most common treatment used initially being 5-ASA.…”
Section: Biologicsmentioning
confidence: 99%
“…Given the rarity of IBDU and the hitherto lack of standardized diagnosis, there are very few studies which have been able to collect treatment information on significant numbers of patients. The aforementioned retrospective study from the Porto group of ESPGHAN utilized the data of 537 children with colonic IBD, including 260 IBDU, to explore common treatment schemes and to compare the treatment outcomes (298). This study demonstrated that treatment for IBDU and UC were broadly similar with the most common treatment used initially being 5-ASA.…”
Section: Biologicsmentioning
confidence: 99%
“…A recent study based on the EUROKIDS registry of newly diagnosed UC reported that 10% of 296 patients with pancolitis had endoscopic evidence of ''backwash ileitis''; however, histologic confirmation was not reported (27). In a subsequent article from the ESPGHAN Porto group, patients with ileitis were included in a cohort of ''indeterminate colitis'' patients, yet the management and outcomes were similar to patients with UC, with lower rates of surgery and good response to aminosalicylates (28).…”
Section: Discussionmentioning
confidence: 99%
“…In both CD and UC, the phenotype at end of follow-up was defined as the most severe phenotype found in the observation period and the phenotype at end of follow-up was used for comparisons, unless noted otherwise. As only a few IBDU patients (n ¼ 14) were included and IBDU previously was found to have a different disease course than CD and possibly also UC, IBDU patients were only included in the prevalence of EIM, but were excluded from further analysis (24).…”
Section: Phenotypementioning
confidence: 99%